RNA-based Therapeutics: Past, Present and Future Prospects, Challenges in Cancer Treatment - Goel, Anjana; Rastogi, Amisha; Jain, Mansi; Niveriya, Kinjal (Current Pharmaceutical Biotechnology, 2024)
It is becoming more and harder in today's climate to disregard the impact of cancer on social health. Even though a significant amount of money is spent annually on cancer research, it still ranks as the second leading cause of death worldwide. Additionally, only about half of the patients suffering from complex forms of cancer survive a year after receiving traditional cancer therapies. A method for silencing genes is called RNA interference (RNAi). Such a method is very effective in focusing on genes linked to cancer. Most gene products implicated in cancer have recently been used as RNA interference (RNAi) therapeutic targets. According to the findings from this research, RNAi application is necessary for today's cancer treatment to target functioning carcinogenic molecules and tumor resistance to chemotherapy and radiation. Proapoptotic and antiproliferative activity has been reported from previous research studies on cell culture systems, animal models, and clinical trials through the knockdown of gene products from RNAi technology. Numerous novel RNAi-based medications are now in the clinical trial stages thanks to the discovery of the RNAi mechanism and advancements in the area. In the future, genomic-based personalized medicines can be developed through this RNAi therapy. Hopefully, cancer sufferers will find this sort of therapy to be one of the most effective ones. Various kinds of RNA-based treatments, such as aptamers, small interfering RNAs, microRNAs, antisense oligonucleotides, and messenger RNA, are covered in broad terms in this study. We also present an overview of the RNA-based therapies that have received regulatory approval in the past or are now undergoing clinical studies.
Keywords: SiRNA